(untitled) (Journal of the College of Education for Women, 2019)
The definition of "prostitute" and prostitution is a difficult one and aquestion over which the legislators of many lands and nations differed. Anotable feature of prostitution is its epidemic increase at times of war,revolution and armed commotion, on account of economic, social andpsychological factors generated by such conditions of mortal conflicts. Warsinvariably deprive young wives and lovers of their men folk, resulting infinancial , sexual and emotional frustrations . At no time is the naturalbalance between the sexes more seriously disturbed than during wars, whenthousands of men are thrown into one sector of the country and hundreds oftowns and villages are left to women and children only. Loaded with bootyprovisions and fat salary, the warrior finds in the starving and displacedwoman an easy target. To the enemy, she is just another victim of war . Thepermanent threat of death and the cheapened price of life diminish thesanctity of human values and at the same time engender a burning desire toensure the survival of human life by a crude response to the sex instinct.Jean Genet’s The Balcony , throws light on the world of whoredom whereMadame Irma and her service carries out her clients’ outrageous fantasies inher "House of Illusions".Finally, the study attempts to diagnose the basic reasons that push womenfor harlotry.